Essays in derivatives :risk-transfer tools and topics made easy /Don M Chance. - Chance, Don M.
This book provides up-to-date coverage of various financial products related to derivatives in several key areas: derivatives and their markets, the basic instruments, derivative pricing, derivative strategies, exotic instruments, and fixed income securities and derivatives. Author Don Chance begins with the basics, defining what a derivative is, outlining four common types - forward contracts, futures contracts, options, and swaps - and explaining the kinds of situations in which one type might be used and preferred over another. Prom there, he gradually moves on to more complex topics - all presented in the same down-to-earth style and nontechnical language."--